The influence of socio-cultural environments on the performance of nascent entrepreneurs: Community culture, motivation, self-efficacy and start-up success - Hopp, Christian; Stephan, Ute (Entrepreneurship and regional development, 2012)
The importance of informal institutions and in particular culture for entrepreneurship is a subject of ongoing interest. Past research has mostly concentrated on cross-national comparisons, cultural values and the direct effects of culture on entrepreneurial behaviour, but in the main found inconsistent results. We add a fresh perspective to this research stream by turning attention to community-level culture and cultural norms. We hypothesize indirect effects of cultural norms on venture emergence: Community-level cultural norms (performance-based culture and socially supportive institutional norms) impact important supply-side variables (entrepreneurial self-efficacy and entrepreneurial motivation) which in turn influence nascent entrepreneurs' success in creating operational ventures (venture emergence). We test our predictions on a unique longitudinal dataset, tracking nascent entrepreneurs' venture creation efforts over a five-year time span, and find evidence supporting them. Our research contributes to a more fine-grained understanding of how culture, in particular perceptions of community cultural norms, influences venture emergence. Based on these findings, we discuss how venture creation efforts can be supported. Our research highlights the embeddedness of entrepreneurial behaviour and its immediate antecedent beliefs in the local, community context.